2005
DOI: 10.1210/jc.2004-0801
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Androgen Receptor Activation Induces Apoptotic Regression of Human Prostate Cancer Cellsin Vitroandin Vivo

Abstract: Nongenomic androgen actions imply mechanisms different from the classical intracellular androgen receptor (iAR) activation. We have recently reported the identification of a membrane androgen receptor (mAR) on LNCaP human prostate cancer cells, mediating testosterone signal transduction within minutes. In the present study we provide evidence that activation of mAR by nonpermeable, BSA-coupled testosterone results in 1) inhibition of LNCaP cell growth (with a 50% inhibitory concentration of 5.08 nM, similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
123
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 36 publications
14
123
0
4
Order By: Relevance
“…12 Earlier binding studies in prostate and colon cancer cells established the optimal concentration of testosterone-HSA treatments. 2,12,16 Accordingly, testosterone-HSA solution was used at a final concentration of 10 27 mol l 21 throughout the study. 12 If not otherwise mentioned, all treatments and incubations with steroids including apoptosis assays were performed in serum-containing medium.…”
Section: Preparation Of Steroid Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Earlier binding studies in prostate and colon cancer cells established the optimal concentration of testosterone-HSA treatments. 2,12,16 Accordingly, testosterone-HSA solution was used at a final concentration of 10 27 mol l 21 throughout the study. 12 If not otherwise mentioned, all treatments and incubations with steroids including apoptosis assays were performed in serum-containing medium.…”
Section: Preparation Of Steroid Solutionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Activation of these binding sites by no permeable testosterone albumin conjugates (TACs), was shown to induce strong proapoptotic and anti-tumorigenic effects on various tumors both in vitro and in vivo. 2,6,8,9 The molecular mechanisms governing these effects have been elucidated and specific signaling cascades triggered by the stimulation of membrane androgen receptors (mARs) have been described in prostate and breast tumor cells. 4,5,[9][10][11] Functional membrane androgen binding sites have been also reported in colon cancer cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a novel membrane-bound AR has been postulated by a number of authors based on the detection of specific androgen binding to plasma membranes in different cell types including endothelial cells [84], breast cancer cells [85], prostate cancer cells [83], osteoblasts [86], macrophages [58], and T-lymphocytes [26; 28; 87]. The ability of androgens to rapidly modulate the activity of ion channels and [Ca 2+ ] i has been observed in several cell types.…”
Section: Membrane Receptorsmentioning
confidence: 99%
“…24 for a recent review). We have previously shown that mAR is expressed in prostate cancer (31), being correlated with the Gleason score, although their activation induces regression of human prostate tumor xenografts (33) and potentiates the effect of cytoskeletal acting agents (34), suggesting a new potential cancer therapeutic target. Finally, in breast cancer cell lines and PC12 pheochromocytoma cells, mER and mAR exert opposing effects on growth, apoptosis, and secretion (34,36).…”
Section: Epo-epor and Steroid Receptors In Breast Cancermentioning
confidence: 99%
“…Steroids, acting via membrane sites, exert short-term pharmacologic actions different from those of intracellular receptors, including ion mobilization, hormone or enzyme secretion, and cytoskeleton modifications (25)(26)(27)(28)(29), possibly involved in several physiologic or pathologic processes, including cancer. Indeed, androgen membrane receptors (mAR) are expressed in human prostate carcinomas (30) and correlate to the differentiation grade of the tumor, expressed by the Gleason score (31), although their activation inhibits the growth of experimental tumors in animals (32,33). In breast cancer cells, estrogen membrane receptor (mER) and mAR exert opposing effects, promoting survival (mER) or apoptosis (mAR; ref.…”
Section: Introductionmentioning
confidence: 99%